Nature, reason, and the good life ethics for human beings - Teichmann, Roger, 1963- (Oxford : Oxford University Press, 2011)
At the centre of our ethical thought stands the human being. Roger Teichmann examines the ways in which facts about human nature determine the shape of ethical concepts such as rationality, virtue, and happiness.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Ethics